DEVELOPMENT OF HIGH TECHNOLOGIES IN INDUSTRY IN THE CONTEXT OF GLOBALIZATION: DIGITAL TWINS - Gnezdova, Julia; Grishina, Vera; Rebrikova, Nadezhda; Kalugina, Svetlana; Ramazanov, Ibragim (Revista Inclusiones, 2020)
The aim of this study is a comparative analysis of the development of high-tech industries that are of global importance for the development and implementation of modern technologies. These technologies are a prerequisite for the presence of Russian enterprises in global high-tech markets, characterized by a shift in the center of gravity in the competition for the stage of development of high-tech products, at the stage of their production. In the modern world, due to the high development of IT, it becomes possible to increase the efficiency of traditional production complexes and achieve the best level of product quality. Applying the paradigm of digital production, with the help of modern IT, it is possible to create digital copies (twins) of individual parts of control objects, each of which describes one of the properties (subsystems, representations) of the object, while they give a complete description of the object in the aggregate, where digital twins are complex information technology systems that cover almost all levels of an automated process control system: from the level of terminal equipment to the level of enterprise resource planning.